The Dividend Policy Intermediary: A Linkage Corporate Governance and Firm’s Value as Empirical Evidence from Metal Sub-Sectors Listed in IDX - Darwin Marasi Purba; Agus Indra P; Eri Marlapa (European Exploratory Scientific Journal, 2022)
This study purposed to explore the empirical evidence of corporate governance i.e. audit committee and audit quality to the firm’s value, then with the dividend policy intermediary. The firm’s value measure utilizes Tobin’s Q proxy, and audit quality uses the big-4 public accounting firm category measurement. The source data consist of secondary data from annual reports of the firm’s metal sub-sector registered on the Indonesian Stock Exchange for the 2013-2019 period, whereas as many as 18 firms. The sampling technique utilized was the purposive sampling method, i.e. the technique of specifying the sample upon spesific judgment. The data analysis used in this study is moderated regression analysis. The results inferred that the audit committee and audit quality do not influence the firms partially. Hereinafter, dividend policy intermediary cannot able a linkage corporate governance both of Audit Committee and Audit Quality towards the dividend policy. The firm size utilizes the dividend policy moderated function to use to become a control variable.